Time-dependent modelling of short-term variability in the TeV-blazar VER J0521+211 during the major flare in 2020 - Abe, S.; Abhir, J.; Abhishek, A.; Acciari, V. A.; Aguasca-Cabot, A.; Agudo, I.; Aniello, T.; Ansoldi, S.; Antonelli, L. A.; Arbet Engels, A.; Arcaro, C.; Artero, M.; et al. (EDP Sciences, 2025)
Self-repairing graphite protective layer has been discovered as a suitable protective layer in blast furnace (BF) hearth in recent years. In the current study, actual samples of self-repairing graphite protective layer taken from a commercial BF were analyzed in detail. The results revealed that the hot face of graphite protective layer exhibits a distinct white graphite luster, with large areas of graphite adhering to the surface. Along the direction of its formation, the sample displays a striped pattern with alternating layers. The graphite is strip-shaped, it is relatively coarse and unevenly distributed. The coarse graphite runs in the same direction, unlike graphite in molten iron which has no fixed direction in a chaotic state. The formation process of selfrepairing graphite protective layer can be concluded, graphite precipitates at the interface through heterogeneous nucleation. Crystal nuclei often preferentially adhere to the surface of these impurities to form, owing to the fact that the nucleation energy of heterogeneous nucleation is lower than that of homogeneous nucleation. Titanium is discovered during the observation of microscopic morphology of graphite protective layer, graphite protective layer is more robust due to the strengthening effect of titanium. Titanium strengthening mechanism of self-repairing graphite protective layer is summarized, the strengthening mechanism can be divided into four steps. TiC particles are dispersed around graphite, which reduces the difficulty of the orientation of flake graphite growth. The presence of TiC increases the growth rate of crystals. The four steps are cyclically performed, so the self-repairing graphite protective layer can precipitate layer by layer through titanium strengthening mechanism, which serves to protect the carbon brick in BF hearth.